BIBLIOMETRIC ANALYSIS OF THE CONCEPT OF CONSUMPTION IN SOCIOLOGICAL STUDIES - Hayrettin Zengin; Yaşar Suveren (Academy Review)
This article presents a bibliometric analysis of academic studies on consumption from 1975 to the present. The study was undertaken to identify trends in consumption publications, understand networks, and outline future research directions. It also evaluated the impact and importance of researchers and specific academic publications using various bibliometric tools, such as citation mapping and co-authorship networks. The research methodology revealed interdisciplinary collaborations and opportunities for further research based on authorship/research network data. Finally, it highlights the benefits of using bibliometric analysis when examining consumption in general. By analyzing sociological publications related to consumption, we hope to convey critical themes prevailing in the field while identifying new avenues for continued research and shared interest across disciplines in future work. The analysis presented in the study is based on examining 1528 publications published between 1975-2022 using bibliometric methods. This study used data from the Web of Science database and comparative analysis using Google Scholar. The findings revealed a significant increase in consumption during the studied period. It was noted that most of the publications were articles written in English. Although sociology-oriented researchers contribute to this field of study, multidisciplinary approaches are also critical. It is expected that research on consumer behavior will continue to be important in the future. Various themes are likely to emerge, such as sustainable consumption, digital habits among consumers, customer satisfaction and happiness, the impact of technological developments on consumption patterns, and how different cultures and groups access consume differently. This study offers an opportunity to understand and analyze consumption practices, behaviors and their consequences within the framework of the discipline of sociology. Due to the interdisciplinary nature of the concept of consumption, it is important to gain a deeper understanding. This study will contribute to international academic literature by identifying trends in consumption publications within the discipline of sociology, identifying social networks, assessing the importance of academic publications, and outlining future research directions.